APPLICATION OF LEGAL RULES RELATED TO DEVIANT SEXUAL BEHAVIOR (EXHIBITIONISM) - Muhammad Faudzi Ahsani; Musakkir; Heriani, Wiwie (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This study aims to examine and analyze the phenomenon of the birth of deviant sexual behavior exhibitionism and examine and analyze the application of legal rules related to deviant sexual behavior exhibitionism. The results showed that The application of laws related to exhibitionism may use the offenses of Article 281 of the Criminal Code, Article 10, and Article 36 of the Pornography Law. The judge has the right to determine whether the defendant's actions can be accounted for or not, whether his soul is sick or not, and can be convicted or not. If the panel of judges believes that the defendant is incapable of responsibility and is convicted, then the defendant is free from punishment but is ordered to be treated in a mental hospital. In determining whether the defendant can be responsible or not, the judge usually asks for the help of a psychiatric expert to examine the condition of the defendant, which is commonly referred to as an expert witness in the trial as evidence listed in Article 184 paragraph (1) of the Code of Criminal Procedure.